The Mystery of Death in Robert Frostâ€™s Poems - Eka Dahlia Ningrum; Masulah - (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2016)
This study analyzed Robert Frostâ€™s poems. There are three purpose of this study: analyze about figures of speech and theme death in Robert Frostâ€™s poems. The writer was choosing Robert Frostâ€™s because he developed a new style of poetry that was metrically precise but which sounded like ordinary American speech. His poetry was full of sentimental expressions about his personal life and conduct. Besides, his poems were simple and profound. He also wrote simple stories about everyday people, often inhabitants of rural New England. Robert Frost wrote extraordinary prose, using simple and direct language; his poems contain symbolism, hidden meanings, sounds, rhyme, meter, metaphors and more. The title of three poems were â€œFire and Iceâ€ , â€œIn a Disused Graveyardâ€ , â€œThe Death of The Hired Manâ€ that taken data from â€œClassic Poetry Series of Robert Frost Poemsâ€ publisher. The method used to analyzed the analysis data was Qualitative Method. This method was chosen because the object if this study does not treat object, and the object can only researched by an observation and description up to the writerâ€™s point of view and match with theory. The result of the study shows that many of figures of speech were used on three of Robert Frostâ€™s poems. They were Metaphor, Symbol, Hyperbole, Assonance, Anaphora, Personification, Paradox, Simile, Antithesis, Alliteration, Irony, Synecdoche and theme death could open the meaning poem as â€œFire and Iceâ€, tells about the end of world between fire or ice. â€œIn a Disused Graveyardâ€, tells about the people wonâ€™t to die. â€œThe Death of The Hired Manâ€ tells about the pity old man suddenly die in his employerâ€™s home.